2007
DOI: 10.1586/14760584.6.5.835
|View full text |Cite
|
Sign up to set email alerts
|

Resiquimod and other immune response modifiers as vaccine adjuvants

Abstract: Synthetic immune response modifiers, such as resiquimod, are Toll-like receptor 7 and 8 agonists that act as vaccine adjuvants, enhancing antigen-specific antibody production and skewing immunity towards a Th1 response. These compounds stimulate dendritic cells to secrete cytokines, upregulate costimulatory molecule expression and enhance antigen presentation to T cells. The compounds have demonstrated vaccine adjuvant properties in a number of animal models. The adjuvant effects can be enhanced by measures th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 91 publications
1
51
0
1
Order By: Relevance
“…In conclusion, reports on the use of TLR7/8 agonists as vaccine adjuvants (Table 1) revealed that the following factors might be crucial for their effectiveness: (a) the route of administration of TLR7/8 ligands, (b) the site of topical imiquimod or resiquimod administration [142], (c) the choice of TLR7/8 agonist, (d) the combination of TLR7/8 agonists with other factors like CD40 stimulation, (e) the route of administration of the antigens [147], and (f) the proximity of the agonist and the antigen [135]. It has not [148], thereby facilitating the design of potent TLR7/8 agonists.…”
Section: How Can Cancer Vaccine Approaches Benefit From Tlr7/8 Ligands?mentioning
confidence: 90%
See 1 more Smart Citation
“…In conclusion, reports on the use of TLR7/8 agonists as vaccine adjuvants (Table 1) revealed that the following factors might be crucial for their effectiveness: (a) the route of administration of TLR7/8 ligands, (b) the site of topical imiquimod or resiquimod administration [142], (c) the choice of TLR7/8 agonist, (d) the combination of TLR7/8 agonists with other factors like CD40 stimulation, (e) the route of administration of the antigens [147], and (f) the proximity of the agonist and the antigen [135]. It has not [148], thereby facilitating the design of potent TLR7/8 agonists.…”
Section: How Can Cancer Vaccine Approaches Benefit From Tlr7/8 Ligands?mentioning
confidence: 90%
“…With this application method, effective anti-OVA or antitumor immune responses were also elucidated, even when OVA peptides were delivered transcutaneously together with imiquimod in an ointment [65,140,141]. Craft et al [78] observed that the antitumor activity of imiquimod was not dependent on direct application of imiquimod to the tumor site, whereas Tomai et al [142] reported that the greater Th1 antibody response was only found if resiquimod was applied at the vaccination site. Differences in their results can be explained by the use of different TLR7/8 agonists (imiquimod versus resiquimod), different models (a live recombinant Listeria monocytogenes vaccine in mice versus an OVA protein vaccination in rats), or the detection of different immune responses (antitumor activity versus antibody response).…”
Section: How Can Cancer Vaccine Approaches Benefit From Tlr7/8 Ligands?mentioning
confidence: 99%
“…In pharmacokinetic studies no systemic side effects were observed following topical administration of imiquimod or other TLR7 agonists because less than 1% of the topically applied imiquimod (5% cream) was absorbed into the body. 25 In addition, topical TLR7 agonist treatment has not been shown to induce production of antibodies against self-antigens or development of systemic autoimmune diseases. 13 Systemic administration of TLR7 agonists requires higher dosages, which might result in some toxicity; specifically, higher doses of TLR7 agonists may result in influenza-like symptoms similar to those observed with IFN-a treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, resiquimod injection may induce systemic cytokine release and thus, must only be formulated to cause local immune activation, preventing systemic effects (68). Parenteral resiquimod has been associated with transient peripheral blood leukopenia and lymphopenia due to general endothelial cell activation with consequent transiently reduced availability of peripheral-blood leukocytes (69).…”
Section: Imiquimod In Lmmentioning
confidence: 99%